Tribological properties of graphene oxide reinforced PPTA/PTFE composites - Hai Wang; Xiaowen Qi; Lifen Liang; Yongfu Wang; Junyan Zhang; Xiangbo Meng (Journal of Materials Research and Technology, 2023)
The tribological properties of the self-lubricating polymer were improved by strengthening the properties of the transfer film. The graphene oxide (GO) reinforced polytetrafluoroethylene (PTFE)/poly-p-phenylene terephthamide (PPTA) composites (GPPs) were prepared by dual-size synthesis. The tribological properties of GPPs were studied on a ball-on-disk tribometer. GPPs have low friction coefficient (minimum = 0.061) and hydrophobicity (maximum = 137.1385°). The structure–property relationships and the practical effect of transfer film enhancement induced by GO were revealed. We attempt to provide guidance for the GO reinforced self - lubricating polymers design. Finally, in light of the excellent properties of GPPs, this study provides guidance for the GO reinforced self - lubricating polymers design.